KEBUDAYAAN PONOROGO DALAM KARTU KUARTET DAN BUKU CERITA BERGAMBAR - Chandra, Nurrul; Candrasari, MC. Wara (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2024)
This study aims to introduce the uniqueness of Reog Ponorogo in a concise and easily understandable manner as a cultural learning tool. It employs engaging storytelling tailored for children aged 12–15 through an illustrated storybook and quartet cards. The research adopts a qualitative methodology with a research-led practice approach. The illustrated storybook and Ponorogo cultural quartet cards for adolescents are visualized using a simplified cartoon style with distortion techniques. Output of the research yields an illustrated storybook titled "Pulang Kampung ke Ponorogo" ("Homecoming to Ponorogo"), which follows the story of Ayuningtyas (nicknamed Tyas) on her first visit to her hometown, Ponorogo. Through the storybook and quartet cards, she explores various cultural elements, including: Reog Ponorogo characters, local flora, traditional foods, tourist attractions, traditional games, performance arts, traditional attire, and Reog musical accompaniments.